Advancing teacher reflective competence: integrating lesson study and didactic suitability criteria in training - Hummes, Viviane; Seckel, Maria José (Frontiers in Education, 2024)
This study examines the impact of combining Lesson Study and the Didactic Suitability Criteria (DSC) for the development of teacher reflective skills. It involves six teachers in an Argentinean training program, spanning 15 virtual sessions over 5 months. Analysis of video recordings indicates significant improvement in reflective abilities, especially when using the DSC for lesson analysis. This approach enhances teaching quality and benefits student learning. The study suggests Lesson Study and the DSC are valuable tools for promoting collaboration and reflection among educators, particularly in math education. Further research with larger samples and long-term follow-up is recommended. This underscores the importance of integrating Lesson Study and the DSC in teacher training to enhance reflective competence and raise education quality.